PPPs for Irrigation: Framework and Insights from Ghana and Tanzania - Meinzen-Dick, Ruth S. (2016)
Presentation by IFPRI's Ruth Meinzen-Dick at the Ninth International Dialogue on Water in Agriculture “Public-Private Partnerships in irrigation: experiences, benefits and risks," June 1-2, 2016, Bonn, Germany